Part Four - Estimates Of Miner Location Accuracy: Westinghouse Location Program “Miner” - I. Introduction (The National Institute for Occupational Safety and Health (NIOSH), 1974)
Crosson and Peters treat the errors that result in miner location due to errors in the overburden earth model used for computing location. A parallel effort by J. Powell of PMSRC is discussed here, where the location method used is that of the Westinghouse location program - "Miner". This location program was tested by Powell by using arrival times generated from the overburden earth model of Table l* rounded to the nearest millisecond. Location computations were then made using 3 geophones at a time. The average location is tabulated for all geophone triplets except when 3 geophones are in line. Geophone arrays were as shown in Tables 2 and 3. The manner in which the test was done is illustrated in Figure 1. I. SUMMARY OF RESULTS The arrival time differences, based on the Table 1 earth model, together with geophone locations based on the array geometries of Tables 2 and 3, were entered into the computer, together with a stated depth of 700 feet and an estimated overburden seismic velocity of 10,000 feet per second. These parameter values were processed by the location program - "Miner". Figure 2 illustrates the interpretation of the plots and data. The tabular data and plots of Table 4 and Figures 3, 4, and 5 illustrate the location error results obtained. These plots indicate that for sources within the array, the errors are considerably less than the measured errors obtained during field tests of the present location system. The possible reasons for this discrepancy are noted in Part Eight (Earth Models).